PENGARUH PENGGUNAAN MEDIA INTERAKTIF BERBASIS CANVA DALAM PEMBELAJARAN IPA TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS VI SD - Hernawati; Encep Supriatna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to examine how sixth-grade students at SDN Sukamulya II's critical thinking abilities are affected when they use interactive media based on Canva to learn Natural Sciences (IPA). Two sixth-grade classrooms at SDN Sukamulya II were chosen at random as part of an experiment using a pretest-posttest control group design. While the control group employed traditional teaching techniques, the experimental group utilized Canva media. With an average pretest score of 70 and a posttest score of 88, the findings demonstrated that students' critical thinking abilities significantly improved when they used Canva. Students also reported feeling more motivated and involved in their studies. According to the study's findings, using interactive media based on Canva helps students develop their critical thinking abilities, and teachers are advised to think about incorporating interactive media into their lessons.